Analisis Pengembangan Geometrik Runway Bandar Udara Fatmawati Soekarno Kota Bengkulu - Sheilla Silvia; Latif Budi Suparma; Suryo Hapsoro Tri Utomo (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
Increasing economic growth requires the organizers of Fatmawati Airport to develop airside facilities. Along with these developments, it is deemed necessary to analyze the development of flexible pavement geometry in existing and future conditions, considering the runway as a place for several flight activities to occur. For this reason, the runway construction itself is capable of receiving and carrying aircraft loads that are appropriately planned. Therefore, this study aims to analyze the geometric development of flexible pavement on the Fatmawati Airport runway and the existing condition of the flexible pavement on the Fatmawati Airport runway, whether it can serve traffic loads until 2041. Analysis of geometric development on the runway is processed using the International Civil Aviation Organization (ICAO). The geometric development of the flexible pavement obtained is then compared with the existing conditions of Fatmawati Airport, Bengkulu City. Based on the runway analysis of Fatmawati Airport, the results of the geometric development of the International Civil Aviation Organization (ICAO) International Civil Aviation Organization (ICAO) rules for runway development should be lengthened by 209 m. These results indicate that the flexible pavement on the Fatmawati Airport runway cannot increase the aircraft load. Bengkulu traffic until 2041, so development is needed. However, the width of the runway has met the classification of 45 m, so there is no need for development.